The C allele of JAK2 rs4495487 is an additional candidate locus that contributes to myeloproliferative neoplasm predisposition in the Japanese population - Ohyashiki, Junko H (BioMed Central, 2012)
BACKGROUND: Polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF) are myeloproliferative neoplasms (MPNs) characterized in most cases by a unique somatic mutation, JAK2 V617F. Recent studies revealed that JAK2 V617F occurs more frequently in a specific JAK2 haplotype, named JAK2 46/1 or GGCC haplotype, which is tagged by rs10974944 (C/G) and/or rs12343867 (T/C). This study examined the impact of single nucleotide polymorphisms (SNPs) of the JAK2 locus on MPNs in a Japanese population. METHODS: We sequenced 24 JAK2 SNPs in Japanese patients with PV. We then genotyped 138 MPN patients (33 PV, 96 ET, and 9 PMF) with known JAK2 mutational status and 107 controls for a novel SNP, in addition to two SNPs known to be part of the 46/1 haplotype (rs10974944 and rs12343867). Associations with risk of MPN were estimated by odds ratios and their 95% confidence intervals using logistic regression. RESULTS: A novel locus, rs4495487 (T/C), with a mutated T allele was significantly associated with PV. Similar to rs10974944 and rs12343867, rs4495487 in the JAK2 locus is significantly associated with JAK2-positive MPN. Based on the results of SNP analysis of the three JAK2 locus, we defined the "GCC genotype" as having at least one minor allele in each SNP (G allele in rs10974944, C allele in rs4495487, and C allele in rs12343867). The GCC genotype was associated with increased risk of both JAK2 V617F-positive and JAK2 V617F-negative MPN. In ET patients, leukocyte count and hemoglobin were significantly associated with JAK2 V617F, rather than the GCC genotype. In contrast, none of the JAK2 V617F-negative ET patients without the GCC genotype had thrombosis, and splenomegaly was frequently seen in this subset of ET patients. PV patients without the GCC genotype were significantly associated with high platelet count. CONCLUSIONS: Our results indicate that the C allele of JAK2 rs4495487, in addition to the 46/1 haplotype, contributes significantly to the occurrence of JAK2 V617F-positive and JAK2 V617F-negative MPNs in the Japanese population. Because lack of the GCC genotype represents a distinct clinical-hematological subset of MPN, analyzing JAK2 SNPs and quantifying JAK2 V617F mutations will provide further insights into the molecular pathogenesis of MPN.